Effect of hydrogen addition on combustion and emissions performance of a gasoline rotary engine at part load and stoichiometric conditions. (1st August 2016) - Ji, Changwei; Su, Teng; Wang, Shuofeng; Zhang, Bo; Yu, Menghui; Cong, Xiaoyu
Highlights: The performance of a H2 -blended gasoline rotary engine was studied. The p, Bmep, T max and ηb increased after H2 blending. Both the CA0-10 and CA10-90 were shortened by the H2 addition. H2 addition resulted in the reduced HC, CO and CO2 emissions. Abstract: The rotary engines may encounter high fuel consumption and emissions due to its narrow and long combustion chamber design. The low ignition energy and high flame speed of hydrogen may help improve the combustion of rotary engines. In this paper, a gasoline rotary engine equipped with gasoline and hydrogen injectors was developed to investigate the combustion and emissions of hydrogen-blended gasoline rotary engines. The engine was run at 3000 rpm and a manifolds absolute pressure of 37.5 kPa with the stoichiometric excess air ratio. The spark timing was set to be 25°CA before the top dead center. The engine was first fueled with the pure gasoline and then blended with the hydrogen. The hydrogen volume fractions in the intake were gradually increased from 0% to 5.2%. The results showed that the combustion pressure, brake mean effective pressure, cylinder temperature and thermal efficiency were simultaneously increased after the hydrogen blending. The crank angle of peak pressure was advanced with the hydrogen addition. The hydrogen enrichment was effective on reducing flame development and propagation periods. HC emissions were reduced by 44.8% when the hydrogen volume fraction in the intake was raised from 0% to 5.2%, CO and CO2 emissions were also reduced after the hydrogen blending.